Spectrum of afibrinogenemia: Bleeding to thrombosis- retrospective analysis of five patients - Sneha Waghela; Sujata Sharma; Nikita Shah; Harshada Uchil; Radha Ghildiyal (Elsevier, 2024)
Background: Afibrinogenemia is a rare disorder, with autosomal recessive inheritance, most often associated with consanguinity. To date, very few cases have been reported from India. The aim was to study the clinical heterogenicity of patients with afibrinogenemia. Case series: We present a retrospective study of five patients with afibrinogenemia diagnosed at our institute. All five patients had bleeding as a primary symptom. The median age for the first episode of bleeding was 150 days (range: 2 days - 18 months). Four were born of third degree consanguineous couple. The male to female ratio was 0.66. One patient had thrombosis along with bleeding. All patients had normal platelet count with deranged prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time, and low to nil fibrinogen levels. All had at least one episode of deep bleeding. The sites of bleeding included: a) intracranial (n = 3), b) intramuscular (n = 1), and, c) hemarthrosis (n = 1). Conclusion: Afibrinogenemia should be considered as a differential diagnosis in patients with bleeding from any site with prolongation of PT and APTT. Paradoxical arterial and venous thrombosis may be a manifestation, but is rare. Thrombotic phenotype requires management with fibrinogen infusion along with anti-coagulants.